2013
DOI: 10.2139/ssrn.2373137
|View full text |Cite
|
Sign up to set email alerts
|

The Operational Evidence Base for Delivering Direct Nutrition Interventions in India: A Desk Review

Abstract: The International Food Policy Research Institute (IFPRI), established in 1975, provides evidence-based policy solutions to sustainably end hunger and malnutrition and reduce poverty. The Institute conducts research, communicates results, optimizes partnerships, and builds capacity to ensure sustainable food production, promote healthy food systems, improve markets and trade, transform agriculture, build resilience, and strengthen institutions and governance. Gender is considered in all of the Institute's work.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 87 publications
0
20
0
1
Order By: Relevance
“…counselling for infant and young child feeding practices; guidelines are under development for paediatric iron folic acid supplementation). Two national programmes, implemented by separate ministries, Ministry of Women and Child Development and Ministry of Health and Family Welfare, operate across the country and are designed to together deliver all of the nutritionspecific interventions through their frontline workers (Avula et al, 2013). There are, however, gaps in the implementation of these interventions, arising from challenges such as operationalizing interministerial convergence, limited understanding of the frontline worker roles and responsibilities, inadequate training, limited mechanisms for supportive supervision, and the burden of multiple responsibilities for frontline workers and other health staff.…”
Section: Policy and Programmatic Context Implementation Guidance Andmentioning
confidence: 99%
“…counselling for infant and young child feeding practices; guidelines are under development for paediatric iron folic acid supplementation). Two national programmes, implemented by separate ministries, Ministry of Women and Child Development and Ministry of Health and Family Welfare, operate across the country and are designed to together deliver all of the nutritionspecific interventions through their frontline workers (Avula et al, 2013). There are, however, gaps in the implementation of these interventions, arising from challenges such as operationalizing interministerial convergence, limited understanding of the frontline worker roles and responsibilities, inadequate training, limited mechanisms for supportive supervision, and the burden of multiple responsibilities for frontline workers and other health staff.…”
Section: Policy and Programmatic Context Implementation Guidance Andmentioning
confidence: 99%
“…As Menon et al (2013) note, sanitation and nutrition interact, so that breastfeeding and improving sanitation, for example, both do more to improve child height when working together. found that if 10 core nutritionspecific interventions were scaled up to 90 per cent, it would only reduce child stunting by about a fifth.…”
Section: Medical Epidemiological and Nutritional Literaturementioning
confidence: 99%
“…Action is needed on all the fronts. In India, there is now broad agreement on the package of direct nutrition interventions targeted to the first 1000 days of life (Avula et al 2013). Without a major shake-up in policy and an improvement in design of the ICDS as well as in the effectiveness of its implementation, the attainment of the goal of fast reduction in HUNGaMA looks unlikely.…”
Section: Summing Upmentioning
confidence: 99%
See 2 more Smart Citations